Neural network-based table tennis competition technique and tactics diagnosis and evaluation - Sun, D. (The Open Cybernetics & Systemics Journal, 2015)
Artificial intelligence technology has rapidly developed; it has already fused into all walks of life. The paper applies artificial intelligence knowledge to make diagnosis and evaluation on China men table tennis players` competition technical and tactics, the paper firstly briefly introduces artificial intelligence method and decision-making tree, rough set, artificial neural network, and then on the basis of artificial intelligence method and table tennis event knowledge to establish table tennis competition technique and tactics diagnosis evaluation indicator system, and make diagnosis on China men table tennis players` competition technique and tactics. Research gets that China men table tennis players should reduce push shot technical errors and improve forehand loop technique in technical aspect, while need to adopt more serve and attack as well as receive and control tactics in tactical aspect.